Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12032-011-9823-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-107 targets cyclin-dependent kinase 6 expression, induces cell cycle G1 arrest and inhibits invasion in gastric cancer cells

Abstract: MicroRNAs (miRNAs) have emerged as post-transcriptional regulators that are critically involved in the pathogenesis of a number of human cancers. Recently, cyclin-dependent kinase 6 (CDK6) is found to be up-regulated in several types of human tumors and has been implicated in cancer initiation and progression. We have identified miR-107 as a potential regulator of CDK6 expression. A bioinformatics search revealed a putative target site for miR-107 within the CDK6 3' untranslated region. Expression of miR-107 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 16 publications
8
85
0
Order By: Relevance
“…They found that the nodal metastasis of endocervical adenocarcinomas is positively associated with the high frequencies of copy number amplification in CDK6 (Hirai et al, 2004). Moreover, suppression of CDK6 can inhibit cell invasion of gastric cancer cells (Feng et al, 2012), which is consistent with our results of cell migration and invasion experiments, despite the accurate mechanisms are still unknown. Taken together, we interpret these results to indicate that let-7a induced downregulation of CDK6, as manifested by subsequent modulation of the expression of its target gene, to impact ES cell growth and metastasis.…”
Section: Discussionsupporting
confidence: 84%
“…They found that the nodal metastasis of endocervical adenocarcinomas is positively associated with the high frequencies of copy number amplification in CDK6 (Hirai et al, 2004). Moreover, suppression of CDK6 can inhibit cell invasion of gastric cancer cells (Feng et al, 2012), which is consistent with our results of cell migration and invasion experiments, despite the accurate mechanisms are still unknown. Taken together, we interpret these results to indicate that let-7a induced downregulation of CDK6, as manifested by subsequent modulation of the expression of its target gene, to impact ES cell growth and metastasis.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, we identified a group of miRNAs transiently upregulated in the early days of muscle regeneration (cluster C, Fig. 2B) including cell cycle-related miR-34c, -107, and -292 (2,18,34). The miR-34 family of miRNAs have been repeatedly implicated as important regulators of the cell cycle and are directly induced by p53 (24).…”
Section: Discussionmentioning
confidence: 94%
“…One example is cyclin D1, which is regulated by miR449a [35] , miR-193b [36] , miR-15/16 [37][38][39] , miR-19a [40] , miR-195 [41] , and miR-302a [42] . The cyclin D1 binding proteins CDK4 and CDK6 are also regulated by a number of miRNAs, including miR-107 [43] , miR-449a [44] , miR-129 [45] , miR-125b [46] , miR-15/16 [39] , miR-24 [47] , miR-195 [41] , and miR-124a [48] . Another important G 1 /S regulator cyclin E, is down-regulated by miR-16 [37] and miR-195 [49] .…”
Section: Mir-34 Familymentioning
confidence: 99%